GAMBARAN HISTOPATOLOGI SINUS INFRAORBITALIS DAN TRAKEA AYAM YANG MENUNJUKKAN GEJALA SNOT PADA PETERNAKAN AYAM DI KABUPATEN KUPANG - Lucyan Maria Azi Owa Milo; Antin YN Widi; Elisabet Tangkonda (Jurnal Veteriner Nusantara, 2020)
Kupang is one of the districts in East Nusa Tenggara Province(NTT) located in Timor Island. Kupang has a large livestock population since livestock has become a source of income for residents in this area. Chicken is the most popular livestock which is reared by farmers in rural areas. Various infectious poultry diseases spread almost evenly in the territory of Indonesia. Snot is one of the respiratory diseases in chickens caused by Avibacterium paragallinarum. Snot cases can be acute or chronic and diagnosed based on rapid disease spreading, clinical symptoms and pathological changes (anatomical and histopathological). The aim of this study is to know the histopathology of sinus infraorbitalis and trachea from chickens snot symptoms derived from farms in Kupang regency. This study used 9 samples of infraorbital sinus and 9 tracheal samples obtained from 9 chickens showing snot symptoms. Necropsy and histopathology technique using Hematoxilline Eosin (HE) staining were applied in this study. Results showed histopathological changes seen in the infraorbital sinuses and trachea are desquamation of epithelial cells, inflammation, haemorrhage, necrosis and the presence of exudate. These histopathological changes are only found in the mucosal, sub mucosal and muscular layer, whereas in adventitia tunica there is no histologic changes.